Simbolisme Perjalanan Nen Dit Sakmas dalam Budaya Kei Kabupaten Maluku Tenggara, Analisis Sosiologi terhadap Identitas Kolektif dan Kearifan Lokal - Johanis Rejaan; Sri Ratna Dewi Lampong; Yusuf Laisow (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to analyze the symbolism of the Nenditsakmas journey as part of Kei culture in Southeast Maluku Regency. This tradition represents the social, spiritual, and moral values ​​of the Kei people that shape their collective identity and local wisdom. Using a qualitative descriptive method, this study positions the researcher as the main instrument in uncovering the meaning of field data. Primary data were obtained through observation and in-depth interviews, while secondary data came from literature studies. Data analysis was carried out through reduction, presentation, and drawing conclusions. The results show that the Nenditsakmas journey has a strong symbolic meaning in shaping the identity and solidarity of the Kei people, while also reflecting respect for the Larvul Ngabal customary law. In the context of modernization, this symbolism still plays an important role in maintaining social harmony and preserving local cultural values. In addition, the philosophical values ​​in Larvul Ngabal and the Ain ni Ain principle are closely related to the ethics, morality, and social order of the Kei people. These values ​​contribute to cultural preservation, mitigating social conflict, and strengthening interpersonal relationships. This research contributes to the development of local cultural studies and serves as a basis for the preservation of the Nenditsakmas ritual. These findings are expected to be a reference for academics, local governments, and cultural communities in designing sustainable cultural preservation policies and programs.